OPTIMIZATION OF THE AQUEOUS SOLUBILITY OF MONOAMMONIUM PHOSPHATE, POTASSIUM NITRATE, AND MAGNESIUM NITRATE VIA THERMODYNAMIC ANALYSIS AND SELECTIVE CRYSTALLIZATION - Ikramov, Muboshir; Zakirov, Bahtiyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study investigates the solubility behavior of monoammonium phosphate (NH₄H₂PO₄, MAP), potassium nitrate (KNO₃), and magnesium nitrate (Mg(NO₃)₂) in aqueous media within binary and ternary systems using a thermodynamic–phase analysis framework. The polythermal (S–T) approach was employed to parameterize the temperature–solubility relationship; the solubility gradient dS/dTand van ’t Hoff plots were used to obtain approximate values of the dissolution enthalpy ΔH_"sol" . Phase diagrams—interpreted via the Gibbs phase rule, Schreinemakers construction, tie lines, and the lever rule—were utilized to delineate crystallization fields. Based on these results, we propose integrated selective-crystallization regimes combining PID-controlled cooling, seeding, on-line refractometry/densimetry, and mother-liquor recirculation.